2008
DOI: 10.1103/physrevc.78.014310
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Schiff moment and soft vibrational modes

Abstract: The atomic electric dipole moment (EDM) currently searched by a number of experimental groups requires that both parity and time-reversal invariance be violated. According to current theoretical understanding, the EDM is induced by the nuclear Schiff moment. The enhancement of the Schiff moment by the combination of static quadrupole and octupole deformation was predicted earlier.Here we study a further idea of the possible enhancement in the absence of static deformation but in a nuclear system with soft coll… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…4), and will be in general much larger than that the value (≈ 50 keV) observed for parity doublets in radium isotopes1. Realistic estimates of Schiff moments for octupole-vibrational systems have yet to be made [32,33]. Nevertheless, it can be concluded that, if measurable CP-violating effects occur in nuclei, the enhancement of nuclear Schiff moments arising from octupole effects in odd-A radon nuclei is likely to be much smaller than for heavier octupole-deformed systems.…”
Section: Discussionmentioning
confidence: 99%
“…4), and will be in general much larger than that the value (≈ 50 keV) observed for parity doublets in radium isotopes1. Realistic estimates of Schiff moments for octupole-vibrational systems have yet to be made [32,33]. Nevertheless, it can be concluded that, if measurable CP-violating effects occur in nuclei, the enhancement of nuclear Schiff moments arising from octupole effects in odd-A radon nuclei is likely to be much smaller than for heavier octupole-deformed systems.…”
Section: Discussionmentioning
confidence: 99%
“…Later this effect was qualitatively observed in the data for other isotope chains [13]. The same idea was useful in the theoretical search [14] for the enhancement of the nuclear Schiff moment, important in the problem of the electric dipole moment, due to the combined action, and therefore correlation, of soft quadrupole and octupole modes [15].…”
Section: Typical Shell-model Resultsmentioning
confidence: 88%
“…Instead of the usual transition dipole operator, we make use of a modified operator which is similar to the so-called Schiff moment from nuclear physics [36].…”
Section: E1 Transitions and Photoabsorbtion Cross Sectionmentioning
confidence: 99%